Kortyzol i testosteron w osoczu krwi u lyzwiarzy figurowych przed olimpiada w Nagano 1998 i w Salt Lake City 2002 - Obminski, Z.; Lerczak, K.; Witek, K.; Starczewska-Czapowska, J.; Olszewska-Lelonkiewicz, M. (Medycyna sportowa, 2003)
Background. The purpose of this publication is to detect changes in the cortisol and testosteron levels as a reaction on different efforts during intensive training. Material and methods. A pair of ice-dance skaters was observed while preparing for Winter Olympic Games (WOG) in Nagano (1998) and in Salt Lake City (2002). Before departing to Nagano, cortisol and testosterone were determined in capillary blood before the afternoon training sessions for 16 consecutive days. The hormones were also determined following a maximal cycle ergometer exercise and following a 4-min ice-dancing programme performed as part of typical training and at Polish Championships. Before departing for Salt Lake City, cortisol, testosterone and lactate responses to two bouts of 10-s exercise, to a submaximal exercise, and twice to 4-min or 2.5-min ice-dancing programmes performed during 4 separate training sessions were determined. All determinations were performed by the same respective methods. Results. Cortisol levels determined at Polish Championsships were in both subjects higher than following maximal laboratory exercises before departing to Nagano. Cortisol levels determined before the Salt Lake City WOG, were in both subjects higher than before Nagano WOG under the same conditions. Cortisol levels in the female partner were on all occasions higher than in the male one. Lactates levels, following competitive ice-dancing did not differ significantly from those observed following maximal laboratory exercises. Conclusion. Ice-dancing competition lasting for a few minutes can be classifield as an anaerobic exercise, which stimulates adrenal cortex and gives blood acidosis.